Approach to the new oral anticoagulants in family practice: Part 2: addressing frequently asked questions - Douketis, James (Can Fam Physician, 2014)
OBJECTIVE: To address common “what if” questions that arise relating to the long-term clinical follow-up and management of patients receiving the new oral anticoagulants (NOACs). SOURCES OF INFORMATION: For this narrative review, we searched the PubMed database for recent (January 2008 to week 32 of 2013) clinical studies relating to NOAC use for stroke prevention in atrial fibrillation and for the treatment of acute venous thromboembolism. We used this evidence base to address prespecified questions relating to NOAC use in primary care settings. MAIN MESSAGE: Dabigatran and rivaroxaban should be taken with meals to decrease dyspepsia and increase absorption, respectively. There are no dietary restrictions with any of the NOACs, beyond moderating alcohol intake, and rivaroxaban and apixaban can be crushed if required. The use of acid suppressive therapies does not appear to affect the efficacy of the NOACs. As with warfarin, patients taking NOACs should avoid long-term use of nonsteroidal anti-inflammatory and antiplatelet drugs. For patients requiring surgery, generally NOACs should be stopped 2 to 5 days before the procedure, depending on bleeding risk, and the NOAC should usually be resumed at least 24 hours after surgery. Preoperative coagulation testing is generally unnecessary. In patients who develop bleeding, minor bleeding typically does not require laboratory testing or discontinuation of NOACs; with major bleeding, the focus should be on local measures to control the bleeding and supportive care, and coagulation testing should be performed. There are currently no antidotes to reverse NOACs. The NOACs should not be used in patients with valvular heart disease, prosthetic heart valves, cancer-associated deep vein thrombosis, or superficial thrombophlebitis. CONCLUSION: Management of “what if” scenarios for patients taking NOACs have been proposed, but additional study is needed to address these issues, especially periprocedural management and bleeding.